The influence of complex military and sports training on the psycho-physiological abilities of university cadets - Vladyslav Otkydach; Mukola Korchagin; Pavlo Potsiluiko; Ihor Fishchuk; Svitlana Indyka; Natalia Bielikova (Jan Długosz University in Częstochowa, 2023)
The article is devoted to the issue of correcting psycho-physiological qualities of VVNIZ cadets. 131 cadets (17-26 years old) participated in the study. They were divided into control (n = 95) and experimental (n = 36) groups. The control group continued to perform the current training program, and the experimental group was engaged in the ICU section. Pedagogical testing was conducted to assess the level of psycho-physiological indicators of abilities. A pretest-posttest method was used to determine the impact of the experimental program on the cadets' psycho-physiological abilities. The reliability of the difference between the indicators of the cadets from the two groups was established using Student's t test (р < 0.05). To investigate the influence of complex military and sports training on the psychophysiological abilities of university cadets. The results of the experiment indicate an improvement in the indicators of professionally important psycho-physiological abilities of the EG representatives in relation to the CG respondents: attention speed improved by 7.9% (р < 0.05), concentration of attention by 15.4% (р < 0.05), mental capacity by 4.4% (p > 0.05), and mental productivity coefficient by 8.3% (p < 0.05). Thus, the means of MSAC can be used to improve professionally important psycho-physiological abilities of cadets of higher military educational institutions.